How reliable is the visual appraisal of a surgeon for diagnosing orbital fractures?. Issue 8 (August 2016) - Dubois, Leander; Jansen, Jesper; Schreurs, Ruud; Habets, Petra E.M.; Reinartz, Susanne M.; Gooris, Peter J.J.; Becking, Alfred G.
Abstract: Purpose: The aim of this study was to evaluate the usefulness of intra-operative visualisation, endoscopic assistance, and CT measurements for estimating the orbital fracture size and complexity. Methods: Ten human cadaver heads were subjected to thin-slice computed tomography (CT). Standardised fractures were created using piezoelectric surgery in accordance with the Jaquiéry classification system. Four surgeons and one anatomist used six different observation methods to visualise and describe the orbital defects. Results: The intraclass correlation coefficients (ICCs) for the fracture length measurements were relatively low for all observation methods (range, 0.666–0.883). CT measurements of width showed high consistency (ICC, 0.910). The surface area of the defect was highly overestimated by all methods (range, 121–184%). None of the observers was able to accurately estimate the length or width of 95% of the defects within an error range of ±0.75 cm. Conclusion: CT measurements are the most consistent and accurate tool for estimating the critical size of orbital factures. In daily practice, a measurement tool in a DICOM viewer could be used, although software packages that allow manual adjustments are advisable. Direct intraoperative visualisation and surgeon experience are of limited value in the estimation of fracture size and complexity, and endoscopy provides no additional advantages.